Simulation applied to improving flow in a public hospital - Lopes, Emilli Cássia Souza; Araújo, Andressa Clara; Pimentel, Cristiane Agra (Brazilian Journal of Production Engineering, 2024)
A well-functioning hospital is essential for providing the best service to patients. Simulation has stood out due to the fact that it provides greater certainty in decision-making and reduces the chances of errors when testing flow changes in the real world. Therefore, the aim of this article is to analyze flows between the central and satellite pharmacies in order to reduce the distance between them as a result of supply times, using an action research methodology, applying Lean tools and simulation in a public hospital in Feira de Santana-BA. After modeling the current scenarios and a future proposal, the results were optimized in terms of drug delivery flow, reducing the distance traveled from 1173.22 m to 125.35 m and consequently the delivery time from 16.47% of the time used to 2.27%.
Keywords: Lean Healthcare; Health 4.0; Simulation